2015
DOI: 10.1016/j.rehab.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Are first ventilatory threshold and 6-minute walk test heart rate interchangeable? A pilot study in healthy elderlies and cardiac patients

Abstract: 6-MWT-HR and VT-HR do not appear interchangeable at the individual level in healthy elderlies and CHF patients. In CAD patients, further larger studies and/or the development of other walk tests could help in confirming the interest of a training prescription based on walking performance, after an exhaustive study of their cardiometabolic requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…The primary outcome was cardiac function, measured by the left ventricular end diastolic diameter (LVDD), [ 27 ] left ventricular ejection fraction (LVEF), [ 28 ] cardiac output (CO), [ 29 ] every cardiac output (ECO), [ 30 ] and cardiac index (CI) [ 31 ] through the color Doppler echocardiography. The secondary outcomes included motor function, measured by the standard 6-MinuteWalk Test (6MWT), [ 32 ] and AEs related to the treatment of SQLXF. All the outcomes were measured before and after 6-month treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome was cardiac function, measured by the left ventricular end diastolic diameter (LVDD), [ 27 ] left ventricular ejection fraction (LVEF), [ 28 ] cardiac output (CO), [ 29 ] every cardiac output (ECO), [ 30 ] and cardiac index (CI) [ 31 ] through the color Doppler echocardiography. The secondary outcomes included motor function, measured by the standard 6-MinuteWalk Test (6MWT), [ 32 ] and AEs related to the treatment of SQLXF. All the outcomes were measured before and after 6-month treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Control group deconditioning was in play. After rehabilitation, Morard et al [ 37 ] reported similar results in patients with coronary disease but not in a healthy elderly population or in chronic heart-failure patients, as also shown by Kervio et al [ 38 ]. Any useful role played by APA intensity in breast cancer patients remains debatable.…”
Section: Discussionmentioning
confidence: 58%
“…Our results agree and reinforce existent literature. Morard et al (2015) reported agreement between HR VT1 in a symptom-limited incremental CPET on a cycle ergometer and HR 6MWT in CAD patients with an acceptable 95% confidence interval of bias from Bland–Altman analysis (−12.3 to 8.1 bpm). Similarly, in patients with chronic heart failure, Oliveira et al (2016) showed a high correlation between HR VT1 and HR 6MWT ( r =0.81; P <0.0001), with an acceptable SEE of 6.05 bpm.…”
Section: Discussionmentioning
confidence: 79%
“…During the 6MWT, all patients used the HR monitor (Polar S810i, Polar Electro Oy, Kempele, Finland) that continuously showed the HR throughout the 6-min test. The highest value of the HR was noted during the last 30 sec of the 6MWT (HR 6MWT ) ( Morard et al, 2015 ). Resting HR was assessed while the patients were standing for 60 sec, after a 5-min rest sitting.…”
Section: Methodsmentioning
confidence: 99%